Determinant Earning Management - Anam, Saiful; Harimulyono, Nurrohman; Istiqomah, Inuk Wahyuni; Pratama, Ade Setia (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study tries to identify "the influence of sales growth, tax planning, firm size and profitability on earnings management (case study of consumer goods sector companies listed on IDX in 2017-2021)" Design/methodology/approach: This analysis comprises all consumer products sector enterprises listed on the Indonesian Stock Exchange (BEI) between 2017 and 2021. Purposive sampling was utilized. This survey included 45 businesses for food and beverage companies listed on the Indonesia Stock Exchange from 2018 to 2021. Findings: Earnings management is somewhat affected by the following elements, which are listed below: when it comes to earnings management, sales growth and profitability have a partial impact; nevertheless, tax planning and firm size do not have a partial impact on earnings management. Practical implications: By concentrating on increasing sales and making strategic tax preparations, businesses can improve their ability to control their profits. Additionally, the size of the company and its profitability are important considerations when it comes to maximizing earnings management. Paper type: Research paper